Demographic, Health, and Exposure Risks Associated With Cognitive Loss, Alzheimer's Disease and Other Dementias in US Military Veterans - Zhu, Carolyn W.; Sano, Mary (Frontiers in Psychiatry, 2021)
The US military veteran population receiving care through the Veterans Health Administration (VHA) is particularly susceptible to cognitive impairment and dementias such as Alzheimer’s disease and related dementias due to demographic, clinical and economic factors. In this report we summarize the prevalence of dementia among US veterans and risks associated with AD and related dementias. We discuss the likelihood that these risks may be increasing in those about to enter the age in which dementias are common. We propose that VHA, the largest integrated health care system in the US, has shown promise in managing health risks that impact dementia prevention and propose further system wide approaches to be assessed for effective dementia prevention and care delivery.